1999
DOI: 10.1089/oli.1.1999.9.13
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cyclopolyamines on the Stability and Conformation of Triplex DNA

Abstract: Linear polyamines are excellent promoters of triplex DNA formation. The effects of structural rigidization of polyamines on triplex DNA stability are not known at present. We wished to develop a series of polyamine analogs as secondary ligands for triplex DNA stabilization for antigene applications. To accomplish this goal, we synthesized cyclopolyamines by interconnecting the two amino or imino groups of linear polyamines with a --(CH2)n-bridge (n=3,4,5). Melting temperature (Tm) data showed that [4,3]-spermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The elasticity of the DNA was correlated to both its interaction with polyamines [43] and temperature. Melting experiments demonstrated that polyamines stabilize the DNA structure with an ability that is a function of the polyamine chain length [24–26]. Moreover, the melting entropy of DNA was determined by measuring the overstretching force of single molecules of DNA [22,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elasticity of the DNA was correlated to both its interaction with polyamines [43] and temperature. Melting experiments demonstrated that polyamines stabilize the DNA structure with an ability that is a function of the polyamine chain length [24–26]. Moreover, the melting entropy of DNA was determined by measuring the overstretching force of single molecules of DNA [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Temperature is an additional factor capable of affecting DNA conformation. It has been reported that (a) an increase of a few°C is associated with a reduction in the overstretching forces of the DNA strands [22,23], (b) that the DNA melting temperature is directly correlated with the chain length of interacting polyamines [24][25][26][27] and (c) that a transition of the DNA chain from a dispersed coil state to a condensed-collapsed state parallels an increase in temperature [28]. These findings draw attention to the relationship existing between temperature and stabilization, aggregation, elasticity and conformational transition of the DNA, all phenomena closely linked to DNA protection and influenced by polyamines.…”
mentioning
confidence: 99%
“…These include the covalent attachment of the duplex intercalator, pyrene, to the end of the oligonucleotide (along with sugar modification at the 2Ј position) or the incorporation of a phosphoramidate backbone consisting of substitution of a nitrogen for the 3Ј-bridging oxygen (31,45). Another approach to stabilize triplexes (and to aid entry into cells) is the use of polyamines either covalently attached to the TFOs or used in conjunction with the oligonucleotides during transfection (46,47).…”
mentioning
confidence: 99%
“…Furthermore, spermine induces the formation of triplex structures under conditions in which triplexes cannot be formed naturally. Various analogues of spermine have been synthesised and studied and some of them, such as cyclopolyamines, have been found to be more efficient . In light of those studies, the formation of DNA triplexes is affected by their length, the type of triplet, and the presence of cations or cationic compounds.…”
Section: Dna Triplexmentioning
confidence: 99%